Cytoreductive surgery and ovarian carcinoma - Balbi, G.; Monteverde, A.; Landino, I.; Amparo Manganaro, et al., M. (Acta Biomedica Atenei Parmensis, 2009)
Purpose of investigation: the aim of this study is to demonstrate if Cytoreductive surgery in patients with ovarian carcinoma increases overall survival. Methods: during the period between 1998 and 2008, 60 patients with a relapse of ovarian cancer, were evaluated in order to undergo a cytoreductive surgery. Results: an optimal cytoreduction (residual disease <1 cm maximum diameter) was obtained in over half of patients. Conclusion: surgery remains the best therapeutic approach in ovarian cancer since it is associated with an increase in survival in all patients undergoing cytoreduction especially in the advanced stages of the disease. These results and those of other studies allow us to determine which patients may benefit from the cytoreductive surgery, improving their survival rate. A disease-free interval > 12 months is the best predictive factor of improved survival rate after surgery.